Effects of Flavonoid Supplementation on Common Eye Disorders: A Systematic Review and Meta-Analysis of Clinical Trials - Davinelli, Sergio; Ali, Sawan; Scapagnini, Giovanni; Costagliola, Ciro (Frontiers in Nutrition, 2021)
Background: Emerging studies show that certain plant compounds may reduce the severity of most prevalent ocular abnormalities. The aim of this systematic review and meta-analysis was to assess the effect of dietary flavonoids on major eye disorders. Methods: Eligible studies were identified by searching PubMed, Web of Science, Scopus, and Cochrane Library databases for all articles published up to April 2021. The literature search yielded 1134 articles, and a total of 16 studies were included in the systematic review. A meta-analysis of 11 intervention trials involving a total of 724 participants was performed. Results: Using a random-effects model, the pooled results revealed an overall significant effect of flavonoids on common ophthalmic disorders (standard mean difference = – 0.39; 95 % CI: – 0.56, – 0.21, p < 0.01). Of the subclasses of flavonoids, flavan-3-ols (standard mean difference = – 0.62; 95 % CI: – 1.03, – 0.22, p < 0.01) and anthocyanins (standard mean difference = – 0.42; 95 % CI: – 0.63, – 0.21, p < 0.01) were the only effective intervention for improving the outcomes of ocular conditions. For several of the other flavonoid subclasses, evidence on efficacy was insufficient. Conclusion: Our findings indicate that flavonoids may improve the clinical manifestations associated with ocular disorders. However, further well-constructed clinical trials are required to confirm these results and examine the effect of flavonoids on eye disorders other than those identified in this review.